Cloud Computing: Redefining Data Management and IT Services in the Digital Age (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This paper delves into cloud computing, a transformative technology reshaping  data management, storage, and IT services. The study explores the fundamentals,  growth, and impact of cloud computing, addressing its advantages and  challenges, with a focus on security, scalability, and cost-efficiency. Through  a comprehensive literature review, this research investigates existing studies,  methods, and findings on cloud adoption across industries. The paper analyses  data from industry reports and surveys, providing insights into cloud adoption  trends and user experiences. The conclusion underscores the potential and  challenges of cloud computing, suggesting directions for future research.
Keywords: Cloud Computing; Data Management; IT Services